Virulence and Antibiotic Resistance Genes in Enterococcus from Wastewater for Reuse and Their Health Impact - Anthony A. Adegoke; Chibuzor E. Madu; Poovendhree Reddy; Opeyemi K. Fatunla; Thor A. Stenström; Anthony I. Okoh (Microorganisms)
Virulence attributes and putative antibiotic resistance genes from enterococcal isolates from wastewater treatment facilities for sustainable reuse and the areas where they discharge treated water were assessed using phenotypic and molecular methods. This analysis was performed on 269 Enterococci, of which 202 were vancomycin-resistant Enterococcus (VRE). VRE strains show markedly higher resistance across multiple antibiotics, especially glycopeptides and beta-lactams, compared to the more susceptible profile observed in vancomycin-susceptible Enterococcus (VSE) strains. vanC was found in every instance of E. gallinarum among VRE and enterococci susceptible to vancomycin (VSE) isolates but not in VR E. faecium/faecalis. Among VRE, 127 (62.9%) possessed at least one of the tetK, tetL, tetM, or tetO, while 22 (17.3%) had two of these genes. The multidrug efflux pump gene emeA was detected in 27 out of 202 (13.4%) VRE isolates and 8 out of 67 (11.9%) VSE isolates. Exactly 69 (78.4%) possessed at least one of the virulence determinants tested, with 10 (11.4%) and seven (8%) positive for haemolysis and gelatinase activity respectively. The gelatinase gene, gelE, was detected in 16 (18.1%) isolates, while more isolates (n = 23; 26.1%) were positive for gelatinase activity. Cytolytic (cyl) genes (1.1%), Angiotensin-converting-enzyme genes (ace) (13.6%), endocarditis-specific antigen A genes (efaA) (25%), hyaluronidase (hyl) genes (9.1%), enterococcal surface protein (esp) genes (4.5%), among others, were detected. Gelatinase activity and the amplified virulence genes were further validated by sequencing the gel-positive amplicons, which were almost identical (98.97%), and the gelE gene of Enterococcus sp. strain SQ07C was deposited under the GenBank accession number PQ381122. Overall, our results showed that the enterococcal isolates were considered as potential pathogens of notable threat to human health via exposure through reuse, and there is a need for more stringent treatment protocols.